The new Arab urban : Gulf cities of wealth, ambition, and distress - Molotch, Harvey Luskin; Ponzini, Davide, 1979- (New York University Press, 2019)
This text is a way to learn from the Persian Gulf - to use its cities, cultures, and politics to broaden our understanding of how wealth and power operate in the world today.